HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN PENGOBATAN PADA PENDERITA DIABETES MELLITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS LEMBURSITU KOTA SUKABUMI - Nur Azizah, Silviani; Saeful Alamsyah, Mustopa; Basri, Burhanudin (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2023)
One of the efforts made to reduce the number of complications of Diabetes Mellitus is to use the four pillars of diabetes mellitus, namely meal planning, physical exercise, medication or pharmacology, and education. The success of a treatment is strongly influenced by the individual himself, such as knowledge of his disease and compliance with his treatment. Family support is the most important thing in influencing treatment compliance for people with diabetes mellitus. The research design used was descriptive analytics with a cross-sectional approach. The number of respondents in this study was 48 respondents. The instrument in this study was a questionnaire. The results of the study were analyzed using the chi-square formula. Results: The results of statistical tests with chi-square p-value generated by 0.003 <0.05 mean that there is a relationship between family support and medication adherence in patients with type 2 diabetes mellitus in the working area of Lembursitu Health Center, Sukabumi City. There is an association between family support and medication adherence among patients with type 2 diabetes mellitus in the working area of Lembursitu Health Center, Sukabumi City.